PERANAN SELOKO DALAM UPACARA ADAT PERKAWINAN MASYARAKAT DI KOTA JAMBI - Gafar, Abdoel (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2014)
This research purpose to give description about part Â of â€œselokoâ€ contained inÂ the tradition of wedding ceremony Jambi society as a form of preservation of localÂ cultural elements jambi especially for â€œselokoâ€. Â The tradition of wedding ceremonyÂ Jambi society has eleven parts in implementation that is time to Â introduction, â€œtegakÂ batuik Â duduk Â bertanyoâ€, Â â€œulur Â antar Â serah Â terima Â adat Â dan Â lumbagoâ€, Â full Â customÂ event, bribery sapat rice, â€œtunjuk ajar tegur sapoâ€, notice and pray.Â The Â role Â of Â seloko Â in Â part Â implementation Â tradition Â  of Â wedding Â ceremonyÂ jambi Â society namely as a media to express feel love in stages in the associationÂ teens â€œberusik sirih berguau pinangâ€, as a partner media choice in mate selectionÂ parts, as a communication media in the part of â€œtegak batuik duduk bertanyoâ€, â€œulurÂ antar pengantin (bride)â€, Â opening ceremonial lanse, as a media to give advice inÂ part of â€œtunjuk ajar tegur sapoâ€, as apologize media, as information media and asÂ media to say pray in part of notice.Keywords: implementation, â€œselokoâ€, tradition of wedding ceremony